The 2022 Kanjuruhan Tragedy: Chronology Analysis, Impact and Social-Legal Review - Damayanti, Nurul Agustin; Fadilla Elza Aida Putri (HM Publisher, 2024)
Humans as social creatures cannot be separated from interaction and potential conflict. Law enforcement is important to regulate people's lives. This research aims to determine the chronology and impact of the 2022 Kanjuruhan tragedy, examine related legal regulations, and review legal and societal aspects. This research is normative juridical research with secondary data and literature study techniques. The study results stated that the Kanjuruhan tragedy which occurred on October 1st, 2022, resulted in many fatalities and injuries. This tragedy left deep wounds and trauma as well as a negative impact on Indonesian football. The Kanjuruhan tragedy is related to law and society. Law Number 11 of 2002 concerning Sports is allegedly one of the factors causing this tragedy. In conclusion, The Kanjuruhan tragedy is a complex human tragedy with far-reaching impacts. There needs to be a revision of regulations, improvements to the governance of football matches, and education for supporters and security forces to prevent similar tragedies.